An Organization's role in anchoring community health: How for-profit hospitals' balance corporate and social responsibility - Kelly Lynn Choyke; Cory Edward Cronin; Vanessa Rodriguez; Brian C. Gran; Berkeley Franz (Elsevier, 2022)
Hospitals serve as anchor institutions by using economic and institutional power to perform community outreach and engagement in ways that benefit local residents. Because the percentage of for-profit hospitals is growing, it is important to understand if and why for-profit hospitals act as community anchors, even if not legally required to do so like more often studied nonprofit hospitals. Using an inductive, qualitative approach, we conducted interviews with 28 for-profit hospital leaders, personnel, and members of hospital advocacy organizations, followed by thematic analysis. Participants believed for-profit hospitals engage in similar anchor activities as nonprofit hospitals due to being motivated by corporate responsibility to shareholders, social responsibility to meet local expectations that hospitals of any type should strive towards healthier communities, and to adapt to the growing focus on health equity. In carrying out anchor work, for-profit hospitals identify strategic reasons to strengthen bonds with potential patient bases and balance both community and business commitments.